Impact of Viral Marketing and Gimmick Marketing on Transformation of Customer Behavior Mediated by Influencer Marketing - Yoesoep Edhie Rachmad; Budiyanto Budiyanto; Khuzaini Khuzaini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid advancement of digital technology has unlocked new opportunities in marketing, especially through social media platforms like TikTok. This study explores the synergy between viral marketing, gimmick marketing, and influencer marketing in driving the transformation of customer behavior from passive consumers to active participants within the digital marketing ecosystem. A quantitative approach was employed, collecting data from 200 respondents actively involved in digital marketing on TikTok as resellers, dropshippers, affiliates, and co-creators. Using the Partial Least Squares method for analysis, the findings reveal that viral marketing significantly influences the transformation of customer behavior. Similarly, gimmick marketing demonstrates a direct and significant impact on this transformation. Moreover, influencer marketing serves as a mediator, amplifying the effects of both viral and gimmick marketing on transformation of customer behavior. This behavioral shift is evident in the transition of consumers from passive roles to active contributors, taking on positions such as resellers, dropshippers, affiliates, and co-creators. At the same time, sellers are evolving from traditional marketing practices to utilizing e-commerce, social media, and live streaming to reach wider audiences. By actively engaging consumers, sellers foster a collaborative ecosystem where consumers play a pivotal role in expanding the marketing framework. To sustain long-term consumer engagement in this digital marketing ecosystem, it is essential to prioritize the selection of credible and relevant influencers while providing continuous education and support for resellers, dropshippers, and affiliates. This research strengthens the theory of planned behavior and the diffusion of innovations theory, offering fresh insights into designing marketing campaigns based on the 4Ps of digital marketing (Platform, Page, Program, and Posting) to address the needs of the digital era.